a: \(\dfrac{4}{7}+\dfrac{3}{4}+\dfrac{2}{7}+\dfrac{5}{4}+\dfrac{1}{7}\)
\(=\left(\dfrac{4}{7}+\dfrac{2}{7}+\dfrac{1}{7}\right)+\left(\dfrac{3}{4}+\dfrac{5}{4}\right)\)
\(=\dfrac{7}{7}+\dfrac{8}{4}\)
=1+2
=3
b: \(\dfrac{5}{2}+\dfrac{6}{11}+\dfrac{3}{8}+\dfrac{7}{2}+\dfrac{6}{8}+\dfrac{5}{11}\)
\(=\left(\dfrac{5}{2}+\dfrac{7}{2}\right)+\left(\dfrac{6}{11}+\dfrac{5}{11}\right)+\left(\dfrac{3}{8}+\dfrac{6}{8}\right)\)
\(=6+1+\dfrac{9}{8}=7+\dfrac{9}{8}=\dfrac{65}{8}\)
c: \(\dfrac{4}{3}-\dfrac{3}{5}+\dfrac{-20}{3}-\dfrac{2}{5}+\dfrac{2}{3}\)
\(=\left(\dfrac{4}{3}+\dfrac{2}{3}-\dfrac{20}{3}\right)+\left(-\dfrac{3}{5}-\dfrac{2}{5}\right)\)
\(=\dfrac{-14}{3}-1=-\dfrac{17}{3}\)
d: \(\dfrac{5}{12}+\dfrac{5}{3}-\dfrac{2}{12}-\dfrac{2}{3}\)
\(=\left(\dfrac{5}{12}-\dfrac{2}{12}\right)+\left(\dfrac{5}{3}-\dfrac{2}{3}\right)\)
\(=1+\dfrac{3}{12}=\dfrac{15}{12}=\dfrac{5}{4}\)